ICT enabled collaborative e-health for cleft lip/palate treatment. (2018) - Choosri, Noppon; Khwanngern, Krit; Yu, Hongnian; Thongbunjob, Krid; Sukhahuta, Rattasit; Natwichai, Juggapong; Boonma, Pruet; Atkins, Anthony; Sitthikham, Suriya
Sophisticated medical treatment often requires a multidisciplinary approach and a number of follow ups. This can limit the opportunity of patients who live in remote areas to access quality and proper treatment due to the fact that healthcare services in Thailand are relatively centralised. The study proposes a collaborative framework to empower local healthcare clusters to service patients in their area of residence more effectively to minimise patient referral to their hub hospital. Several common features and constraints are identified. The investigation is to develop a practical ICT solution based on a case study of cleft-lip/palate treatment using a network in Northern Thailand. Initial implementation of this enterprising project is outlined in this paper. The current progress includes two applications that have been developed to address the high priority issues of collaborative networking. One is to support data sharing for medical teams and the other is to facilitate patients to access better medical services.